Dampak Implementasi Rekam Medis Elektronik terhadap Waktu Tunggu dan Kepuasan Pasien IGD - Rahman, Arif; Paramarta, H. Vip; Istiqomah, Syafa; Rohmawan, Hanung Choiri; Prabowo, Hanif Agung; Putri, Melati Triani (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the impact of Electronic Medical Record (EMR) implementation on waiting time and patient satisfaction in the Emergency Department (ED) of Muhammadiyah University Hospital Semarang (RS UNIMUS). A qualitative descriptive approach was employed through in-depth interviews, direct observation, and document analysis of hospital policies. The study involved six key informants directly engaged in the implementation of EMR, including two emergency physicians, two nurses, one administrative officer, and one medical record staff member. The findings reveal that EMR implementation has a positive impact on service efficiency, particularly in patient registration and medical data recording, leading to a significant reduction in waiting time. The system also improves data accuracy and integration among hospital units, thereby enhancing interprofessional coordination and communication. The success of EMR implementation at RS UNIMUS is influenced not only by technological readiness but also by organizational support, staff competence, and the gradual development of a digital work culture. Consequently, the adoption of EMR contributes to improved emergency service quality and reinforces the hospital’s digital transformation toward data-driven and efficient healthcare delivery within a teaching hospital context.